2021
DOI: 10.3390/ijerph182111608
|View full text |Cite
|
Sign up to set email alerts
|

Source Apportionment of Fine Organic Particulate Matter (PM2.5) in Central Addis Ababa, Ethiopia

Abstract: The development of infrastructure, a rapidly increasing population, and urbanization has resulted in increasing air pollution levels in the African city of Addis Ababa. Prior investigations into air pollution have not yet sufficiently addressed the sources of atmospheric particulate matter. This study aims to identify the major sources of fine particulate matter (PM2.5) and its seasonal contribution in Addis Ababa, Ethiopia. Twenty-four-hour average PM2.5 mass samples were collected every 6th day, from Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…The high clustering of satellite-based ambient PM 2.5 in the Eastern and Southeastern Amhara, Eastern Tigray, and Afar areas might be attributed to the country's major importexport highway route passing through these areas [69]. A one-year study with weekly PM 2.5 sampling (n = 62) in Addis Ababa indicated that traffic flows contributed to 28% of the mass of PM 2.5 , which perhaps might be aligned with the sources of import-export highway vehicles [70]. Additionally, due to PM 2.5 's nature as a regional pollutant, it is transported to other nearby areas [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high clustering of satellite-based ambient PM 2.5 in the Eastern and Southeastern Amhara, Eastern Tigray, and Afar areas might be attributed to the country's major importexport highway route passing through these areas [69]. A one-year study with weekly PM 2.5 sampling (n = 62) in Addis Ababa indicated that traffic flows contributed to 28% of the mass of PM 2.5 , which perhaps might be aligned with the sources of import-export highway vehicles [70]. Additionally, due to PM 2.5 's nature as a regional pollutant, it is transported to other nearby areas [33].…”
Section: Discussionmentioning
confidence: 99%
“…In Afar and Eastern Tigray, in particular, the consumption of agricultural residues (animal dung and crop stalks and stubbles) as cooking fuel is higher due to the scarcity of woody biomass [72]. Biomass sources are the second biggest contributors to PM 2.5 in cities of developing countries [73] including Addis Ababa (18.3%) [70]. The Afar region is a relatively arid area with less tree coverage and is home to the Danakil desert.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 502 deaths (4.44%) were attributable to current air pollution levels referenced to the 35 μg/m 3 WHO interim target annual level and 2043 (17.7%) at the WHO 10 μg/m 3 annual guideline [8]. There are different estimates sources emission estimations; from vehicular sources (28%), biomass burning (18.3%), plus soil dust (17.4%) comprise about two-thirds of the mass PM 2.5 , followed by sulfate (6.5%) [9].…”
Section: Effect Of Air Pollution On Human and Ecosystem Healthmentioning
confidence: 99%
“…"=yxvwtv |wQ Q@ xDiQo s=Hv= |=yR}r=v; " [23] "Ovm ltm QiUtD= QO |oOv}q; `@=vt `@=vt |Ov@syU hrDNt |=yVwQ R= xO=iDU= OvtR=}v =wy QO jrat C= QP pQDvm w G}=Dv G= QNDU= 'OvwW ?=NDv=CMB pOt |OwQw u=wva x@ |rY= |xOvQ}PB |rm p}=iwQB R= u=wD|t G}=Dv Ow@y@ |= Q@ "OUQ|t Q_vx@ |Q=wWO Q=m |k]vt w pt=m R= =} w CU= xOW u} wOD Q_vOQwt C}=U |= Q@ |v=O}t CQwYx@ xm QDj}kO `@=vt x@ = QH= |= Q@ CMB pOt 'OW xDio QDV}B xm Qw]u=ty "OQm xO=iDU= 11 |@}mQD pOt |= Q@ `@vt p}iwQB xm |]}=QW QO '=yVwQ u} QDy@ R= |m} "OQ=O R=}v `@=vt |=yp}iwQB =} PCA |=ypOt =OD@= xm CU= u}= 'OW=@ xOWv u}}aD w x@U=Lt Q_vOQwt C}=U pOt x@ |OwQw u=wvax@ =yu; |HwQN TBU w = QH= OwHwt |=yxO=O |= Q@ PMF [20] "OwW xO=O CMB 'OwW|t OQ=w CMB pOt x@ |OwQw u=wvax@ xm `@vt p}iwQB 'Q}N= VwQ QO PMF =} PCA |=ypOt |HwQN xm |rt=wa w 12 xOW |Q}oxR=Ov= `@vt u=wva x@ |}=U=vW pt=wa u}@ R= Qo = "OvwW|t |Q=Pos=v 13 xOW G= QNDU= `@vt u=wvax@ 'OvDUy G= QNDU= `@vt 'OW=@ xOW |Q}oxR=Ov= `@vt `@vt p}iwQB l} sQi x@ |rt=a 'xOW `wv R= 'OW=@ `@vt p}iwQB OvJ =} wO R= |@}mQD Qo = w 14 xO=U `wv R= QwmPt |xOW [20] "CU= 15 ?mQt =} PCA |=ypOt \UwD 16 =yxvwo C_re |rm |=yxO=O 'pw= |xrLQt QO `@=vt p}iwQB w CmQ=Wt OYQO 'pw= |xrLQt |HwQN "OvwW|t R}r=v; PMF 'OW xDio R}v QDW}B xm Qw]u=ty 'u}vJty "CU= EC-Source w ES-Source "OwW|t jq]= xDN=vW=v `@vt u; x@ xm 'Ov=t|t |k=@ xDN=vW=v =yCmQ=Wt R= |WN@ pOt x@ x}wv=F |xOvQ}PB O}OH |xOvQ}PB u=wva x@ EC-Source 'swO |xrLQt QO |Ov@xDUO '`@=vt O=OaD %Ovv=t |RH C=aq]= CU= Qm P x@ sRq "OwW|t OQ=w CMB C=aq]= R= EC-Source QO `@=vt CmQ=Wt OYQO p}Uv=DB OQwt QO '""" w `@=vt |xOvQ}PB QO OwHwt ptDLt |xOW xQ=W= `@=vt x@ "O};|t CUOx@ |k}kL |=}vO G}=Dv |Ov@`tH =@ 'C}=yvQO "OwW|t xDio 17 xOW |Q}oxR=Ov= `@vt Q} R 'x}wv=F |xH}Dv 'Msub-source w ES-Source CmQ=Wt OYQO Q}N= |xrLQt wO `@=vt G= QNDU= w |@}mQD pOt |Q}oQ=mx@ =@ "OwW|t pY=L |@}mQD pOt |}=yv u=mt= w QDxO=U x} wv=F |xOvQ}PB 'Oa@ |xrLQt QO =yu; hPL w ES-Source QO xOvvmCmQ=Wt `@=vt O=OaD `k=w QO "OwW|t sy=Qi |QDj}ta |UQQ@ w p}rLD |xOvQ}PB QO xm |a@=vt O=OaD =@ =yu; T=}k x@ xHwD =@ swO |xrLQt x} wv=F |xOvQ}PB QDtm xDN=vW=v `@=vt syU OYQO |iQ] R= "OwW|t QDtm 'OvQ=O CmQ=Wt |rY= 'OvwW|t |}=U=vW `@=vt |t=tD xm Ow@ u}= Q@ ZQi CMB pOt QO OwW|t p}=i QO xm OvDUy |a@=vt u=ty xDN=vW=v `@=vt "Ow@v Qw]u}= C}ak=w QO =t= xOvQ}PB w `@vt j}@]D sOa w |Q=oR=U=v Ea=@ w Ov=xOt=}v `@=vt p}=iwQB |wDLt |xOvQ}PB w hPL x} wv=F |xOvQ}PB R= xDN=vW=v `@=vt 'xOW xQ=W= VwQ =@ =t= "OvwW|t |rm Ov}=Qi '2 pmW QO [21] "Ovvm|t =O}B |QDW}@ j}@]D u; `@=vt Q} R w x} wv=F xOy=Wt |@}mQD pOt QO xOv}q; O}rwD `@=vt l}miD |xwLv w xOW Qm P |R=UpOt "OwW|t pOt |HwQN |wQ CU= sRq CMB w PCA G}=Dv u}@ \=@DQ= Qw_vt x@ CMB pOt |OwQw =@ ?U=vDt u; |HwQN =D OwW s=Hv= |}=yVR=OQBPCA OYQO |x@U=Lt Qw_vt x@ |]N |xQ}eDtOvJ uw}UQoQ R= wQ u}= R= [12] "OwW |}=}t}W xvwoQy |DmQ=Wt C_re u= R}t w PCA R= xOt; CUOx@ pt=wa CmQ=Wt j}irD R= 'Q[=L VywSB QO Qo}O u=}@x@ [12] "OwW|t xO=iDU= hrDNt pt=wa QO |=}= Rt R= |Q}oxQy@ Qw_vt x@ |rY= |=yxir - , = Q}N= CU= j <RH =@ \@DQt |=y|Q}oxR=Ov= x@ \w@Qt C}a]k sOa xj 'u; QO xm :4 |x]@= QOwW|t ^=Lr R}v `@vt p}iwQB x@ \w@Qt C}a]ksOa [W ] T} QD=t QO wjj = 1…”
mentioning
confidence: 99%